(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
The condition attached to matrimonial consent (Canon 1102) between canonical and ecclesiastical law The study analyses the institution of the condition attached to matrimonial consent in Latin canon law (can. 1102), examining its legal nature, distinctive characteristics and implications when deliberating ecclesiastical sentences, issued on the basis of this ground of nullity, in the Italian legal system. The research highlights the peculiarity of this institute, which represents a specificity of Latin canon law with respect to both the Eastern Churches and the Italian civil legal system. Through a systematic analysis, some of the different types of condition (suspensive, resolutive, merely permissive) and their interrelations with other institutes of canon matrimonial law are examined, with particular attention to the simulation of consent. The research suggests a differentiated approach to the deliberation of sentences based on proper and improper conditions, highlighting the complexity of the institute and its relevance in the dialogue between canon and civil law, offering interpretative cues for a more effective harmonization between the two legal systems. SOMMARIO: 1. Cenni introduttivi - 2. Funzione della condizione apposta al consenso matrimoniale - 3. Breve descrizione di alcune tipologie di condizione - 3.1. La distinzione tra condizione sospensiva, risolutiva e meramente potestativa - 4. Considerazioni sulla delibazione delle sentenze ecclesiastiche di nullità matrimoniale pronunciate sulla condizione apposta al consenso - 5. Conclusioni.